2008
DOI: 10.1590/s0066-782x2008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Dosagem de microalbuminúria em hipertensos e em pacientes portadores de doença coronariana

Abstract: SummaryBackground: The normal 24-hour albumin excretion rate is of 20 mg. A persistent rate of 30 to 300 mg/day is called microalbuminuria and is related to a higher prevalence of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
1
0
2
Order By: Relevance
“…A study in hypertensive patients showed an association between albuminuria and age, obesity, dyslipidemia and diabetes. That study also pointed out that the presence of albuminuria may represent an important predictor of coronary artery disease (SILVA et al, 2008). It is of note that effort dyspnea is an early sign of coronary disease and mediated by transient diastolic dysfunction in ischemia (GIPSON et al, 2019), which could explain the finding of this study.…”
Section: Discussionsupporting
confidence: 66%
“…A study in hypertensive patients showed an association between albuminuria and age, obesity, dyslipidemia and diabetes. That study also pointed out that the presence of albuminuria may represent an important predictor of coronary artery disease (SILVA et al, 2008). It is of note that effort dyspnea is an early sign of coronary disease and mediated by transient diastolic dysfunction in ischemia (GIPSON et al, 2019), which could explain the finding of this study.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the frequency of microalbuminuria found in the patients with reduced GF was 14.6% in the AH group without DM and 17.6% in the AH group with DM. National studies report a prevalence of microalbuminuria of 9.5% and 13.7% in hypertensive individuals undergoing treatment 37,38 . Such variations in prevalence can be attributed to differences in the methods of analysis of urinary excretion of albumin, due to variation sin age ranges, ethnicity or comorbidities in the studied groups 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Essa prevalência está próxima às encontradas em estudos realizados anteriormente, 13,23 inclusive em nosso País. 24,25 Em relação aos achados ecocardiográficos, pudemos observar que os pacientes hipertensos com microalbuminúria apresentaram maiores espessuras das paredes ventriculares e espessura relativa da parede (p < 0,05). Pontremoli, em estudo realizado com 211 pacientes hipertensos não tratados, encontrou associação significativa entre microalbuminúria e aumento das espessuras do septo e parede posterior do ventrículo esquerdo.…”
Section: Discussionunclassified
“…Sabe-se que a microalbuminúria pode ser afetada por obesidade, exercício físico extenuante, consumo excessivo de álcool, cigarro, sobrecarga salina ou proteica, infecção urinária e gravidez. 12,25 Dentre as limitações do presente estudo, destacam--se em relação aos grupos que não foram abordados isoladamente os pacientes portadores de diabetes e soma-se o fato de que os nossos pacientes se encontravam fazendo uso de medicações, enquanto em alguns estudos foram utilizados pacientes sem medicação. 13,15 Quanto à coleta urinária da microalbuminúria, utilizamos apenas uma amostra enquanto houve estudos que utilizaram de duas a três amostras, embora existam estudos nos quais foi realizada apenas uma coleta com resultados satisfatórios, inclusive utilizando amostra isolada de urina.…”
Section: Discussionunclassified